(untitled) - Miller, Robert H. (San Francisco, 2006)
Campus Confidential is the ultimate insider's guide to surviving and thriving in college. Written in a friendly, conversational style, Campus Confidential offers a comprehensive, chronological treatment of the college experience by the author, a Yale graduate, and a blue-ribbon panel of fourteen diverse "mentors" from colleges and universities around the country. But this is not just another fluff-filled freshman handbook. Campus Confidential is the complete guide to the college experience-providing solid, road-tested advice for every stage of the process, from high school students getting ready to apply, to college seniors looking for jobs or applying to graduate school, and everything in between.
Keywords: College student orientation,College students; United States,United States